Urbanization and GDP per capita: New data and results for the Polish lands, 1790–1910. Issue 4 (2nd October 2019) - Bukowski, Maciej; Koryś, Piotr; Leszczyńska, Cecylia; Tymiński, Maciej; Wolf, Nikolaus
Abstract: Polish lands in 19th century are usually located in the economic peripheries of Europe. However there are no usable datasets of Polish GDP for this period to verify this hypothesis. The main problem is lack of reliable and comparable macroeconomic data from country divided between Russia, Austria and Prussia. The main goal of this research was to propose the method based on the urbanization data set to estimate the GDP of Polish territories and to verify the hypothesis on the peripheral development of Polish lands. In result the new estimates on GDP per capita were established, that allowed to confirm the hypothesis of semi-peripheral development of Polish territories in 19th century and slow process of catching-up with the core economies.